A Prospective, In Vitro, Randomized Study to Compare Two Media for Donor Corneal Storage. Issue 9 (September 2016) - Basak, Soham; Prajna, N. Venkatesh
Abstract : Purpose: To determine if Cornisol is as effective as Optisol-GS as an intermediate-term corneal storage medium. Methods: A prospective, in vitro, randomized, partially masked study using paired donor corneas. Optical grade tissues not suitable for surgery were used. After performing baseline slit lamp evaluation, one tissue of each pair was randomly stored in Cornisol and the mate in Optisol-GS. Specular microscopy images were taken at baseline and repeated on days 3, 7, 10, and 14. The endothelial cell loss, endothelial cell density (ECD), coefficient of variance, and percentage hexagonality were recorded. On the 14th day, endothelial vitality was assessed histologically with alizarin red-S and trypan blue dual staining. The histology images were analyzed with ImageJ software and correlated with baseline specular findings. Results: A total of 32 pairs of cornea were included. One pair was excluded because of turbidity in both media. The mean donor age, death to preservation time, and baseline slit lamp characteristics were comparable between the 2 groups. The endothelial cell loss over 14 days was 17.4% in the Cornisol group and 15.7% in the Optisol-GS group ( P = 0.83). The ECD, coefficient of variance, and percentage hexagonality were comparable between the groups at all measurement periods. There was no significant difference in the ECD calculated from histology pictures using ImageJ program (2345 ± 239 in Cornisol vs. 2393 ± 341 in Optisol-GS group; P = 0.22) and showed positive correlation using Pearson coefficient with baseline specular findings. Conclusions: Cornisol is as effective as Optisol-GS in preserving the donor corneal tissues for 14 days.